Spin-orbit interaction in a generic vortex field transmitted through an elliptic fiber - Alexeyev, C.N.; Soskin, M.S.; Volyar, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Any small external perturbation on an ideal round optical fiber induces cross - section deformation and transforms eigen guided vortices into generic vortex fields, which can change their structure and angular momentum. It is the properties of these vortical fields in an elliptic weakly guiding optical fiber that we consider in this paper. The eigenfunctions and the spectrum of polarization corrections to the scalar propagation constant in the case of relatively large and small values of a fiber ellipticity are obtained by means of the spin-orbit interaction operator method. Discussed is the conversion process of a spin and orbit angular momenta on a vortex propagation along a deformed fiber.